Enhancing Early Childhood Artistic Skills Through Angklung at Kindergarten - Arifin - Muhammad; Khairunnisa Khairuunisa; Nabilah - Araminta; Hilda Zahra Lubis (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
Music plays a central role in children's development, and the use of musical instruments such as the angklung has become part of the music education curriculum in preschools. This research aims to delve into the application of the angklung in developing the artistic abilities of early childhood. The method employed is a qualitative approach with descriptive qualitative methods, utilizing data analysis steps based on the Miles and Huberman approach. Data collection involves interviews, observations, and documentation. The research results indicate that the angklung is effective in developing the artistic abilities of children, particularly in the realm of musical arts. Children exhibit variations in their musical expressions through the use of the angklung. These findings provide a comprehensive understanding of the potential of the angklung as a tool for developing the artistic skills of early childhood.